Efficacy of Aqueous Extract And Essential Oil of Cinnamon in Decontaminating Chicken Meat - Badhe, Shekhar R; M.N., Fairoze.; D., Rathnamma.; H, Manjunatha (Journal of Meat Science, 2011)
Cinnamon (Cinnamomum zeylanicum) of the family Lauraceae is a commonly used spice in India. This study was designed to evaluate the antimicrobial efficiency of aqueous extract and essential oil of cinnamon on food borne pathogens. Essential oil of cinnamon (Minimal Inhibitory Concentration (MIC) of 1:1000) was effective against reference strains of Salmonella typhimurium, Escherichia coli (MTCC 452), Staphylococcus aureus, Escherichia coli O157 and Bacillus cereus, whereas, aqueous extract of cinnamon even at 100 per cent concentration did not produce significant zone of inhibition against the test organisms such as Bacillus cereus, Staphylococcus aureus, Salmonella typhimurium, E. coli O157. Dilutions of essential oil of cinnamon at 1:150 and 1:250 concentrations brought more reduction in bacterial counts compared to 1:500. The concentration of 1:150 was more efficient in decontaminating chicken meat surface among the concentration tried. Aqueous extract of cinnamon at 100 and 75 per cent concentrations did not have any effect in decreasing the viable bacterial pathogens.